Cuidados paliativos: o que tem sido publicado em revistas de terapia ocupacional da América Latina no período de 2009 a 2018? - FARIAS, Aline Lobato de (2023)
ABSTRACT: Introduction: Palliative Care is a model of health care directed to people who have life-threatening diseases that are beyond the therapeutic possibility of cure. Within the patient care in palliative care there is a multiprofessional team composed of several health professionals, including the occupational therapist, who is responsible for favoring the maintenance of occupational life. The scientific journals, among them, the specific ones of Occupational Therapy are an alternative of dissemination of what has been developed on certain subject. Objective: To investigate what has been published in occupational therapy journals of Latin America regarding palliative care. Methodology: This is a literature review than that provides an overview with a bibliographic search in 10 occupational therapy journals in Latin America from 2009 to 2018. Results / Discussion: Eleven publications were selected to be part of this study, found in four occupational therapy journals. Final Considerations: Publication in journals, besides generating knowledge and new opportunities for the dissemination of professional practice, allows the expansion of the discussion of research in Occupational Therapy and Palliative Care.